Alastair Gunn and Ruth Walker. Buddhism and Environmental Ethics In Context Kuala Lumpur : Centre for Civilisational Dialogue University Of Malaya, 2003 - Bucher, Stephen (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The book introduces various approaches from the viewpoint of secular environmental ethics. The first one is that of moral extensionism which extends moral status to the welfare and rights of animal and the ecosystems. The other approaches refer to the holistic environmental ethics, deep ecology, and eco-feminism. Similarities and differences of these various perspective to Buddhist teachings are then pointed out. Buddhism actually does not have an explicit project of environmental ethics. There is no such need as Buddhism does not make a sharp distinction between humans and nature. Instead it emphasizes mutual interdependence of things, and it has an eco-centric view. Religions with anthropocentric views have usually shown less concern for the environment. Also, Buddhism does not expound an ethic of stewardship. It rather considers humans as neighbors to the other less intelligent beings.